COPD is frequent in conditions of comorbidity in patients treated with various diseases in a university hospital - Yamasaki, Akira (Dove Medical Press, 2010)
BACKGROUND: Chronic obstructive pulmonary disease (COPD) is one of the leading causes of death and loss of disability-adjusted life-years. However, many COPD patients are not diagnosed because of underrecognition or underdiagnosis of this disease among many patients and physicians. One possible reason is underrecognition of spirometry. In this study, we examined the prevalence of airflow limitation and underlying disease in patients with airflow limitation. METHODOLOGY: From April 2006 to March 2008, patients who had spirometry performed were examined. The original disease of patients, pulmonary function tests, smoking status, and respiratory symptoms were surveyed from their medical records. RESULTS: Of all patients who had spirometry performed, 15.8% showed airflow limitation (FEV(1)/FVC < 0.7). A variety of diseases were observed in patients with airflow limitation. Among all diseases, cardiovascular disease was the highest and gastrointestinal malignant disease had the second highest prevalence in patients with airflow limitation. CONCLUSION: COPD might be frequent in conditions of comorbidity in patients treated for various diseases. Attention should be paid to the possibility of co-existence of COPD and the influence of COPD on these patients.